A Giant Pedunculated Urothelial Polyp Mimicking Bladder Mass in a Child: A Rare Case - Mehmet Kaba; Sultan Kaba; Tacettin Yekta Kaya; Hüseyin Eren; Necip Pirinççi (Case Reports in Pediatrics)
Ureteral fibroepithelial polyps are rarely seen benign tumors with mesodermal origin. These polyps can involve kidney, pelvis, ureter, bladder, and urethra. The most common symptoms are hematuria and flank pain. The choice of treatment is either endoscopic or surgical resection of polyp by sparing kidney. Here, we presented a pediatric case with giant, fibroepithelial polyp that mimics bladder tumor, originating from middle segment of the ureter.